Evaluation of Inclusive Education Policies at the Level of Primary and Secondary Education in Indonesia - Munawir Yusuf; Salim Choiri; Mahardika Supratiwi (Department of Special Education, 2017)
This study examines the implementation of inclusive education at the elementary and secondary level of education in Indonesia through 9 dimensions, namely institutional dimension, curriculum dimension, learning dimension, assessment dimension, student dimension, human resource dimension, the dimension of facilities and infrastructure, and financing dimensions. This study uses a survey approach involving 82 elementary, junior high schools, vocational schools that provide inclusive education from 16 districts/cities in 7 Provinces in Indonesia. A sample of Province of Regency / City and educational unit selected by purposive random sampling. Data collection of the Self-Evaluation Instrument of Inclusive Schools from Yusuf (2014) covering Form 1, 2, and 3. Data analysis used descriptive statistics with 5 categories (0-20%), less (21% - 40%), moderate (41% - 60%), good (61% - 80%) and very good (81% - 100%). The results show that the implementation of inclusive education at the primary and secondary education unit level is as follows: (1) the average institutional aspect of 62%; (2) aspects of the curriculum averaging 71.1%; (3) average learning aspect 53,1%; (4) assessment aspect and average grade increase 60,9%; (5) student aspect average 54,6%; (6) aspects of human resources averaging 45.8%; (7) aspects of facilities and infrastructure averaged 22.1%; (8) aspects of community participation averaged 50.8%; and (9) average financing aspects of 45.4%.Penelitian ini mengkaji tentang implementasi pendidikan inklusif di tingkat satuan pendidikan dasar dan menengah di Indonesia melalui 9 dimensi, yaitu dimensi kelembagaan, dimensi kurikulum, dimensi pembelajaran, dimensi penilaian, dimensi kesiswaan, dimensi SDM, dimensi sarana dan prasarana, dimensi peran serta masyarakat, dan dimensi pembiayaan. Penelitian ini menggunakan pendekatan survei dengan melibatkan 82 SD, SMP, SMK yang menyelenggarakan pendidikan inklusif dari 16 Kabupaten/Kota pada 7 Provinsi di Indonesia. Sampel Provinsi Kab/Kota dan satuan pendidikan dipilih secara ppurposif random sampling. Pengumpulan data Instrumen Evaluasi Diri Sekolah Inklusi dari Yusuf (2014) yang meliputi Form 1, 2, dan 3. Analisis data menggunakan statistik deskriptif dengan 5 kategori yaitu sangat kurang (0 – 20%), kurang (21% - 40%), sedang (41% - 60%), baik (61% - 80%) dan sangat baik (81% - 100%). Hasil penelitian menunjukkan bahwa implementasi pendidikan inklusif di tingkat satuan pendidikan dasar dan menengah sebagai berikut: (1) aspek kelembagaan rata-rata 62%; (2) aspek kurikulum rata-rata 71,1%; (3) aspek pembelajaran rata-rata 53,1%; (4) aspek penilaian dan kenaikan kelas rata-rata 60,9%; (5) aspek kesiswaan rata-rata 54,6%; (6) aspek sumber daya manusia rata-rata 45,8%; (7) aspek sarana dan prasarana rata-rata 22,1%; (8) aspek peran serta masyarakat rata-rata 50,8%; dan (9) aspek pembiayaan rata-rata 45,4%.